Settlement of Workers' Rights at PT Satelit Bintang Persada Through PKPU Legal Efforts at the Medan Commercial Court - Nadapdap, Gindo; Sulistiawan, Hendrik; Alfarisi, Salman (Jurnal Penelitian Medan Agama, 2024)
Generally, if a company is no longer able to provide for the welfare of its employees, then the company experiences a financial crisis and this will result in the company's bankruptcy. Bankruptcy or bankruptcy is legal certainty received by the debtor because of the court's bankruptcy decision. The result of bankruptcy is that the debtor's assets are placed under investment so that the debtor cannot have his assets back. The problem is that this research was conducted to reveal how the rights of PT workers are resolved. Bintang Persada Satellite through legal action at the Medan District Court and how the PKPU was resolved at the Medan Commercial Court. The research method uses normative juridical research methods. The research results show that PT. Bintang Persada Satellite was found guilty and had to pay workers their rights in accordance with the provisions of article 156 of Law no. 13 of 2003 which includes severance pay, long service awards and rights assignment money. Meanwhile, in the case of delayed debt payment obligations (PKPU) which occurred at PT. Bintang Persada Satellite where the company is deemed incapable and is no longer actively running its busines.